Development Of Professional Training Of Students In Higher Education As A Factor Of Quality Specialist Training - Yavkochdiyeva Dilafruz Egamkulovna (Zien Journals, 2022)
In higher education, the development of their professional qualities and professional abilities, the need to ensure the professional development of students, the achievement of professional improvement in the continuation of the student's educational and cognitive activity, mastering, personality change, development of experience and competences and professional qualities determine the priority directions of systematic reform of higher education, possessing modern knowledge and high moral, the issues of raising the process of training highly qualified personnel who think independently to a qualitatively new level, modernization of higher education, the importance of developing social sphere and economic sectors on the basis of advanced educational technologies, the importance of restoring a perfect educational system based on the rich spiritual potential and universal values of the people and the latest achievements.
Keywords: education; process; result quality; guarantee